Effect of Different Repolishing Procedures on The Color Change of Alkasite - Seda Nur Karakaş; Cihan Küden (Cumhuriyet University, 2022)
Objectives: An esthetic restoration with an unacceptable color is the main cause for replacement of anterior tooth restorations. The aim of this study is to evaluate the effect of repolishing on the color change of the new material group of alkasite after exposure to coffee solution. Materials and Methods: Alkasite material placed in Teflon molds with a diameter of 8 mm and a height of 2 mm was polymerized under the application of mylar strip and a total of 32 samples were obtained. The samples were randomly immersion into groups. Group R: Diamond grained polishing rubbers, Group D: Aluminum oxide discs are applied and the polishing process is completed. After the first color measurement was made, it was immersed in coffee and the measurement was repeated 1 week later. L was divided into two groups (n=8) and repolished with rubber (RR) and discs (RD). In the D group, re-polishing was done with rubber (DR) and disc (DD) and color measurements were repeated. Results were analyzed by using one-way ANOVA and Tukey test at 95% confidence interval. Results: The greatest color change (ΔE00) was in group R. At the end of seven days, similar color change values were found between the groups of R and D (p > 0.05). There is no difference between the RR and RD groups. Significantly less color change was observed in the DD group than in the RR and RD groups (p = .003, p = .042, respectively). Similarly, the DR group showed less color change than the RR group (p = .015). Conclusions: The color stability of the alkasite was affected by the polishing procedure. The repolishing process reduced the color change, but not at a clinically acceptable level.